Soroepidemiologia de agentes virais de equinos de vaquejada na região de Mossoró/RN - Ferreira, Heider Irinaldo Pereira (2016)
Samples of horses of vaquejada were collected in activity, male and female, breed Quarter Horse and Paint Horse, aged between 2 and 15, from rural and urban areas of the city of Mossoró, located in the West region of Rio Grande do Norte state. Tests were performed on 132 serum samples for antibodies to vesicular stomatitis (EV) and equine viral arteritis (AVE) 118 for encephalomyelitis east and west (EEL/EEO) 114 for herpesvirus type 1 (HVE-1) and 61 to equine influenza (IE). Techniques used varied according to the studied disease; antibodies against EV (Ribeirão and Alagoas), equine viral arteritis, HVE-1 and EEL / EEO been researched by virus neutralization test in Vero cell cultures (EV, verify HVE-1 and EEL/EEO; and search for the IE type 2 (H3N8) was performed by inhibition of hemaglutination technique. The following results of the samples tested were obtained: for AVE no positive animals (n = 132) for EV was obtained 39 (29.55%) positive animals Alagoas type and 6 (4.54%) for the animals Ribeirao type (n = 132) with respect to encephalomyelitis, antibodies against and EEO EEL (n = 118) were present in 13 (11.01%) and 1 (0.84%), respectively; for EHV-1 were found 22 (19.29%) positive horses (n = 114). Regarding historical variable respiratory and reproductive diseases, it was statistically significant (p=0.02) for the presence of antibodies against EHV-1. The AVE is not present among the equine vaquejada in Mossoró/RN, for other surveyed viruses (EV, IE, EHV-1, EEL and EEO) there is evidence of viral activity in populations of equine Mossoro, and respiratory clinical signs and reproductive may be suggestive of infection by EHV-1